THE ROLE OF ACCOUNTING DIGITAL TRANSFORMATION IN REDUCING COSTS AND ITS IMPACT ON THE COMPANY'S PERFORMANCE: AN APPLIED STUDY (World Economics and Finance Bulletin, 2024)
The research purposes to identify the role of accounting digital transformation represented by (technologies, Process digitisation, databases, human resources) in reducing costs represented by (resource management, rationalization of losses, and continuous improvement) and its reflection on the company's performance represented in (employee satisfaction, improving productivity, and growth) among a sample of workers in the Kufa Cement Plant, and the research sought to address an important problem represented in What is the role of accounting digital transformation in reducing costs and its reflection on the performance of companies?, Aware of the basis of this adopted the research descriptive analytical approach in identifying and building variables, as the research adopted the questionnaire tool in collecting the data necessary to apply the variables at the Kufa Cement Factory and through that distributed (130) questionnaire to workers to measure the level of each variable of the research variables, and retrieved them (123) questionnaire, by (113) questionnaire valid for analysis, and (10) damaged questionnaires, To get the best results, the programme (SPSS&AMOS. V.28), and the research presented several results, foremost of which was the existence of an integrative role for the digital transformation of accounting in reducing costs and its reflection on the company's performance, and this in turn contributed to improving the capabilities of the research laboratory by focusing on the mechanisms of accounting digital transformation in determining its transactions in order to reduce costs and improve the performance of the laboratory, and accordingly the research recommended the need to adopt digital accounting systems that provide access to needed data and information anywhere, which reduces the costs of infrastructure, As well as the need to implement accounting analysis tools to extract valuable insights that improve financial performance and identify areas to improve the company's performance efficiently and effectively.
Keywords: accounting digital transformation; cost reduction; company performance